Application of polydopamine-modified triphasic PLA/PCL-PLGA/Mg(OH)2-velvet antler polypeptides scaffold loaded with fibrocartilage stem cells for the repair of osteochondral defects - Cheng, Renyi; Xie, Tao; Ma, Wen; Deng, Peishen; Liu, Chaofeng; Hong, Yuchen; Liu, Changyu; Tian, Jinjun; Xu, Yanhua (Frontiers in Bioengineering and Biotechnology, 2024)
Articular cartilage defects often involve damage to both the cartilage and subchondral bone, requiring a scaffold that can meet the unique needs of each tissue type and establish an effective barrier between the bone and cartilage. In this study, we used 3D printing technology to fabricate a tri-phasic scaffold composed of PLA/PCL-PLGA/Mg(OH)₂, which includes a cartilage layer, an osteochondral interface, and a bone layer. The scaffold was filled with Velvet antler polypeptides (VAP), and its characterization was assessed using compression testing, XRD, FTIR, SEM, fluorescence microscopy, and EDS. In vitro investigation demonstrated that the scaffold not only supported osteogenesis but also promoted chondrogenic differentiation of fibrocartilage stem cells (FCSCs). n vivo experiments showed that the tri-phasic PLA/PCL-PLGA/Mg(OH)2-VAP scaffold together with FCSC, when transplanted to animal models, increased the recovery of osteochondral defects. Those results demonstrate the promising future of illustrated tri-phasic PLA/PCL-PLGA/Mg(OH)2-VAP scaffold loaded with FCSCs as a new bone and cartilage tissue engineering approach for osteochondral defects treatment.